If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3N + -5)(3N + 5) = 0 Reorder the terms: 2(-5 + 3N)(3N + 5) = 0 Reorder the terms: 2(-5 + 3N)(5 + 3N) = 0 Multiply (-5 + 3N) * (5 + 3N) 2(-5(5 + 3N) + 3N * (5 + 3N)) = 0 2((5 * -5 + 3N * -5) + 3N * (5 + 3N)) = 0 2((-25 + -15N) + 3N * (5 + 3N)) = 0 2(-25 + -15N + (5 * 3N + 3N * 3N)) = 0 2(-25 + -15N + (15N + 9N2)) = 0 Combine like terms: -15N + 15N = 0 2(-25 + 0 + 9N2) = 0 2(-25 + 9N2) = 0 (-25 * 2 + 9N2 * 2) = 0 (-50 + 18N2) = 0 Solving -50 + 18N2 = 0 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '50' to each side of the equation. -50 + 50 + 18N2 = 0 + 50 Combine like terms: -50 + 50 = 0 0 + 18N2 = 0 + 50 18N2 = 0 + 50 Combine like terms: 0 + 50 = 50 18N2 = 50 Divide each side by '18'. N2 = 2.777777778 Simplifying N2 = 2.777777778 Take the square root of each side: N = {-1.666666667, 1.666666667}
| 5x+1=x+1 | | 5-39=10x-17x | | 3x^2=72x | | 9x-60=5x-8 | | x+11=2x+5 | | (5x+4)-(2x-4)= | | x+13=3x+3 | | x-1=3x+5 | | 120-5x=13x+16 | | 132-5x=22x+15 | | 5a=45+2q | | 12-8x=48-22x | | y=x^2+3x+1 | | 10+4x=22 | | 6x^2=39x-45 | | 0=x^2(x^4+6x^2-16) | | 12x+24=8x+4 | | -2x-13=x+2 | | -2-13=x+2 | | 6-10x=66-45x | | -x^2+18x+19=0 | | 2x+6=x+1 | | 5x+10y= | | ln(3x)+ln(5)=2 | | 2x-2=x+6 | | 7x+22=5x+50 | | 6-10x=46-24X | | 5x^2+26x+24= | | 4n-5=27 | | -3x-4=x+24 | | 5a-40=a | | 10x-118=4x-10 |